Using of opportunities of graphic processors for acceleration of scientific and technical calculations - Dudnik, V.A.; Kudrjavtsev, V.I.; Sereda, T.M.; Us, S.A.; Shestakov, M.V. (Вопросы атомной науки и техники, 2009)
The new opportunities of modern graphic processors (GPU) for acceleration of the scientific and technical calculations with the help of paralleling of a calculating task between the central processor and GPU are described. The description of using the technology NVIDIA CUDA for connection of parallel computing opportunities of GPU within the programme of the some intensive mathematical tasks is resulted. The examples of comparison of parameters of productivity in the process of these tasks' calculation without application of GPU and with use of opportunities NVIDIA CUDA for graphic processor GeForce 8800 are resulted.